Perlindungan Hukum terhadap Konsumen dan Tanggung Jawab Pelaku Usaha Akibat Iklan yang Menyesatkan - Feynita Susilo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study delves into the vital subject of legal protection for consumers and the responsibilities of business actors in light of misleading advertising. This research focuses on a qualitative research approach examining the mechanisms available to safeguard consumers' rights and to hold businesses accountable for deceptive advertising practices. Based on the positive legislations in the field of consumer protection and advertising along with various views of experts, the following analysis intends to explain how the legal products in this country offer forms of resolution regarding the many cases of deceptive advertising. The research concludes that a comprehensive legal framework, which includes both non-judicial and judicial avenues, is essential to ensure the effective protection of consumers and the imposition of responsibilities on business entities involved in misleading advertising. This study sheds light on the multifaceted nature of consumer protection within the legal landscape, emphasizing the need for a balanced approach to uphold the interests of both consumers and businesses.